2006
DOI: 10.1590/s1806-37132006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Manifestações extra-esofágicas da doença do refluxo gastroesofágico

Abstract: Gastroesophageal reflux disease often presents as heartburn and acid reflux, the so-called "typical" symptoms. However, a subgroup of patients presents a collection of signs and symptoms that are not directly related to esophageal damage. These are known collectively as the extraesophageal manifestations of gastroesophageal reflux disease. Principal among such manifestations are bronchospasm, chronic cough and laryngitis, which are classified as atypical symptoms. These manifestations comprise a heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
15

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 62 publications
0
17
0
15
Order By: Relevance
“…In infants, GER and microaspiration produce not only gastrointestinal symptoms such as regurgitation and vomiting, but also respiratory symptoms including nocturnal cough, otitis media, sinusitis, chronic cough, recurrent bronchiolitis and pneumonia [20, 21]. Microaspiration repeatedly irritates the airways resulting in inflammation that causes bronchospasm and airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In infants, GER and microaspiration produce not only gastrointestinal symptoms such as regurgitation and vomiting, but also respiratory symptoms including nocturnal cough, otitis media, sinusitis, chronic cough, recurrent bronchiolitis and pneumonia [20, 21]. Microaspiration repeatedly irritates the airways resulting in inflammation that causes bronchospasm and airway remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Microaspiration repeatedly irritates the airways resulting in inflammation that causes bronchospasm and airway remodeling. Irritation of the vagus nerve due to GER increases the incidence of bronchospasm and hyper-responsiveness [20, 22]. An animal study has also demonstrated that GER and microaspiration are major risk factors in developing respiratory symptoms [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the principal evidence that GERD is the cause of chronic cough is based on the resolution of the symptoms after an efficacious antireflux treatment. [33]…”
Section: Discussionmentioning
confidence: 99%
“…Considerada afecção digestiva de elevada prevalência e incidência em ascensão, a doença do refluxo gastroesofágico (DRGE) compromete a qualidade de vida dos pacientes, em virtude da gravidade das complicações, intensidade e diversidade dos sintomas (9,16,20,25,26,28,31) . O diagnóstico clínico da DRGE é bastante sensível, pois a maioria dos pacientes apresenta os sintomas clássicos da doença, representados por pirose e regurgitação.…”
Section: Introductionunclassified